2013
DOI: 10.1007/s10517-013-2164-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of Renomedullary Interstitial Cells of Hypertensive ISIAH Rats

Abstract: The structural characteristics of the renal medulla and its interstitial cells were studied in hypertensive ISIAH rats (in comparison with normotensive WAG rats) in order to clear out the role of the renomedullary interstitial cells in the mechanisms of AP regulation. Morphometric electron microscopic analysis and immunohistochemical studies in ISIAH rats detected the initial signs of the renomedullary sclerosis. The renomedullary interstitial cells of ISIAH rats were characterized by higher numerical density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The upregulation of the podocyte-expressed MIF induces an injury of podocytes and accelerates the progression of glomerulosclerosis [57]. In ISIAH rats, the upregulation of Mif gene was found both in renal cortex [9] and in renal medulla (the current study), and possibly may contribute to development of atherosclerosis as well as to glomerulo- and medullary sclerosis histologically determined earlier [7, 8]. …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The upregulation of the podocyte-expressed MIF induces an injury of podocytes and accelerates the progression of glomerulosclerosis [57]. In ISIAH rats, the upregulation of Mif gene was found both in renal cortex [9] and in renal medulla (the current study), and possibly may contribute to development of atherosclerosis as well as to glomerulo- and medullary sclerosis histologically determined earlier [7, 8]. …”
Section: Discussionsupporting
confidence: 56%
“…The development of the hypertensive state in ISIAH rats is also accompanied by a hypertrophy of the left ventricle, increase in the wall thickness of the small arteries, and changes in the electrocardiographic pattern [6]. The studies on the kidney histology showed the alterations, which were indicative of an increase in filtration barrier functional load and of processes leading to the development of glomerular [7] and medullary sclerosis in ISIAH rats [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Comparative electron microscopic study of glomerular apparatus in 6-month old ISIAH and Wistar rats showed hypertrophy of renal corpuscles in hypertensive kidney, accompanied by multiple structural changes such as capillary narrowing or dilation, endothelial flattening, podocyte hypertrophy and flattening of their cytopodia, thickening of basal lamina, mesangial volume expansion and increase in the number of intercapillary processes of mesangial cells [ 21 ]. Besides, the renal medullary interstitial cells of ISIAH kidneys were characterized by higher numerical density and were enlarged with a higher volume share of their secretory granules [ 22 ]. Complex of these signs suggested a disturbance of glomerular capillary blood circulation and a functional podocyte stress, compensating the microcirculatory disturbances.…”
Section: Resultsmentioning
confidence: 99%
“…Complex of these signs suggested a disturbance of glomerular capillary blood circulation and a functional podocyte stress, compensating the microcirculatory disturbances. Changes in basal membranes and mesangium are indicative of not only increase in filtration barrier functional load, but also of initial stages of glomerular [ 21 ] and renomedullar sclerosis [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ISIAH rats also show a number of other characteristic features of hypertensive state: hypertrophy of the left ventricle, increase in the wall thickness of the small arteries, and changes in the electrocardiographic pattern [ 7 ]. ISIAH rats are also characterized by increased kidney mass [ 8 ] and some alterations in kidney histology indicative of increase in filtration barrier functional load and of initial stages of glomerular [ 9 ] and renomedullar sclerosis [ 10 ]. These features, the genetically determined enhanced responsiveness to stressful stimulation, and the predominant involvement of the neuroendocrine hypothalamic-pituitary-adrenocortical (HPA) and sympathoadrenal systems during the disease development let to consider the ISIAH rat strain as an advantageous model of the human stress-sensitive hypertensive state [ 11 ].…”
Section: Introductionmentioning
confidence: 99%